2014
DOI: 10.1177/1077546314543726
|View full text |Cite
|
Sign up to set email alerts
|

Smart damping of fuzzy fiber reinforced composite plates using 1--3 piezoelectric composites

Abstract: This article is concerned with the investigation of active constrained layer damping (ACLD) of smart laminated fuzzy fiber reinforced composite (FFRC) plates. The distinctive feature of the construction of this novel FFRC is that the uniformly spaced short carbon nanotubes (CNTs) are radially grown on the circumferential surfaces of carbon fibers. The effect of CNT waviness on the damping characteristics of the laminated FFRC plates is investigated when wavy CNTs are coplanar with either of the two mutually or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Based on average bond-dissociationenthalpies, Zeinalipour-Yazdi and Loizidou [34] applied physical sphere-in-contact models to elucidate the cap geometry of single walled CNT with sub-nanometer width (i.e., (3,3), (4,4) and (5,5)-SWCNTs). Their DFT calculations reveal that these new carbon geometries have similar stability to carbon found in other ball-capped zigzag and arm-chair nanotubes (i.e., (5,5), (6,6), (9,0) and (10,0)). Recently, experimental and theoretical investigations reported that creating nanoscale non-centrosymmetric pores in graphene nanoribbons would lead to apparent piezoelectric behavior [35,36].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on average bond-dissociationenthalpies, Zeinalipour-Yazdi and Loizidou [34] applied physical sphere-in-contact models to elucidate the cap geometry of single walled CNT with sub-nanometer width (i.e., (3,3), (4,4) and (5,5)-SWCNTs). Their DFT calculations reveal that these new carbon geometries have similar stability to carbon found in other ball-capped zigzag and arm-chair nanotubes (i.e., (5,5), (6,6), (9,0) and (10,0)). Recently, experimental and theoretical investigations reported that creating nanoscale non-centrosymmetric pores in graphene nanoribbons would lead to apparent piezoelectric behavior [35,36].…”
Section: Introductionmentioning
confidence: 84%
“…, and are the bond vectors. 6 The following changes occur in the x-component of the coordinate of the i th atom when the graphene sheet is subjected to uniaxial or shear strains:…”
Section: Tb Modeling Of Electronic Structure Of Graphenementioning
confidence: 99%
“…Among all others, CNTs have been emerged as the ideal candidates for multifarious applications due to their remarkable thermoelastic and physical properties. The quest for utilizing the remarkable thermomechanical properties of CNTs has led to the emergence of a new area of research that involves the development of nanocomposites . These studies revealed that the addition of a small fraction of CNTs into a polymer matrix introduces significant improvement in the multifunctional properties of microcomposites and nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that adding a small amount of CNTs in a polymeric matrix can considerably improve the mechanical properties of the resulted nanocomposite [15][16][17][18][19][20]. Also, some research works have presented the successful use of piezoelectric fiber in the smart damping of CNTRC structures [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%